Psychotropics use and occurrence of falls in hospitalized patients: A matched case‐control study. Issue 3 (12th January 2022) - Morishita, Chihiro; Ichiki, Masahiko; Shimura, Akiyoshi; Ishibashi, Yoshiki; Inubuse, Atsuo; Masuya, Jiro; Inoue, Takeshi
Abstract : Aim: Several studies have suggested the use of psychotropics as a possible risk factor for falling. However, there were several limitations to these previous studies, such as the use of data obtained from administrative databases and the lack of information about the time interval between psychotropics use and falling. Therefore, in this study, we aimed to assess the association between psychotropics use and falling in hospitalized patients, using reliable data collected from medical records. Methods: A matched (age, sex, and inpatient department) case‐control study of patients hospitalized at Tokyo Medical University Hospital was performed using the new‐user design, based on data extracted from medical records. The outcome was the occurrence of falls. The use of four classes of psychotropics (antipsychotics, antidepressants, anxiolytics, and hypnotics) was compared between 254 cases (patients who experienced falls) and 254 controls (patients without falls). Multivariable logistic regression analysis was performed to clarify the associations between falling and the use of these psychotropics. Results: Univariable analyses demonstrated that the use of every class of psychotropic was statistically significantly associated with falling. Moreover, the association of the use of hypnotics with falls remained significant in the multivariable logistic regression model built including potential confounding factors, such as age, sex, inpatient department, body mass index, fall risk score measured by a fall risk assessment sheet completed on hospital admission, and the use of other classes of psychotropics. Conclusions: Our findings suggest that the use of hypnotics may be a risk factor for falling in hospitalized patients.